Characterizing rural livelihoods in a changing environment: a case study in the High Atlas Mountains of Morocco - Adele Woodmansee; Meryem Aakairi; Bruno Gérard; Omar Saadani Hassani; Abderrahim Ouarghidi; Alison G. Power; David G. Rossiter; Andrew McDonald (Discover Sustainability)
Abstract The High Atlas Mountains of Morocco are recognized as a global hotspot for rapid environmental change, but there is limited information about how communities and households are responding. Rural livelihoods that are dependent on agriculture are highly vulnerable to intensifying climate extremes, especially when these stressors intersect with long-term socioeconomic trends, including out-migration to urban centers. In 2022–2023, we carried out a a household survey and focus group discussions to understand the evolution of livelihood strategies in four Amazigh villages in Imegdal Commune in the western High Atlas. Results suggest that water shortages are causing cropping systems to simplify, as households stop planting some crop species and reduce the area planted of others. Households are also reducing livestock numbers in response to drought and reductions in labor availability created by migration. Other natural resource-based activities, including beekeeping and collecting wild herbs, are being abandoned. This study suggests that decreasing precipitation is rapidly undermining the viability of agricultural activities in the High Atlas. In the absence of viable adaptation strategies, this could lead to a profound restructuring of rural livelihoods across the region.